Axonal Fusion via Conduit-Based Delivery of Hydrophilic Polymers. (December 2015) - Sexton, Kevin W.; Rodriguez-Feo, Charles L.; Boyer, Richard B.; Del Corral, Gabriel A.; Riley, David C.; Pollins, Alonda C.; Cardwell, Nancy L.; Shack, R. Bruce; Nanney, Lillian B.; Thayer, Wesley P.
Background: Hydrophilic polymers have been shown to improve physiologic recovery following repair of transected nerves with microsutures. Our study was designed to combine hydrophilic polymer therapy with nerve tubes (NT) to enhance polymer delivery to the site of nerve injury. Methods: Using a rat sciatic nerve injury model, a single transection injury was repaired in an end-to-end fashion with NT+polyethylene glycol (PEG) to NT alone. Compound action potentials (CAPs) were recorded before nerve transection and after repair. Behavioral testing was performed for 5 weeks. Results: PEG therapy restored CAPS in all, but one, animals, while no CAPS were recorded in animals not receiving PEG. Behavioral nerve function was measured using the standardized functional assessment technique and foot fault asymmetry scores (FF). FF scores were improved for the PEG therapy groups on postoperative days 7, 14, and 21. However, after expected eventual axonal outgrowth, the benefit was less noticeable at days 28 and 35. Immunohistochemistry of the distal axon segments showed an increase number of sensory and motor axons in the NT+PEG group as compared to NT alone. Conclusion: These data suggest that PEG delivery via a conduit may provide a simple, effective way to fuse severed axons and regain early nerve function. For proximal nerve injuries in large animals, recovery of axonal continuity could dramatically improve outcomes, even if fusion only occurs in a small percentage of axons.